MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI KEGIATAN FINGER PAINTING PADA ANAK USIA 5-6 TAHUN DI TK PERTIWI LENGGADAI HILIR KABUPATEN ROKAN HILIR - Ulin Lestari; Daviq Chairilsyah; Febriliasmanto Febriliasmanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this study is less improve motor skills in the fine motor skills of children through finger painting, some children may not be able to explore the various media and activities, using the stationery correctly, in accordance with the pattern cutting, sticking to the right, to express themselves through movement drawing in detail. Therefore, the need to increase the fine motor skills of children through finger painting. The purpose of this study was to determine whether there is an increase in the fine motor skills of children through finger painting and to find out how the increase that occurred. This research is a classroom action research conducted in two cycles. Data collection tool used in this study is in the form of observation sheet. Sabjek in this research were 15 children 7 boys and 8 girls. Based on the analysis of the assessment process of the second cycle increased. Improvement occurred, ie from before the action to the first cycle of 24.65%, the first cycle to the second cycle of 41.08%, and increased from the prior cycle to cycle II of 75.87%. From the results of these studies concluded that through finger painting can improve fine motor skills of children aged 5-6 years in kindergarten Pertiwi Lenggadai Downstream Rokan Hilir.Keywords: Fine Motor Skills, Finger Painting